Network Governance for Strengthening Coastal Community Economies Based on Blue Economy: Evidence from Southwest Papua Province, Indonesia - Rahman Rahman; Muh. Akmal Ibrahim; Sukri Sukri; Didik Iskandar (Journal Social Civilecial, 2025)
Coastal blue-economy governance in Southwest Papua Province involves diverse actors and resources, yet a tight paradox persists between actor plurality and the weakness of equitable and productive relations. Networks have formed empirically through inter-governmental cooperation, conservation funding, and customary practices, but the quality of these relations remains uneven. This study analyses network governance in coastal blue-economy development through Klijn and Koppenjan’s (2000) four-dimensional framework: actors and relations, resources, rules, and perceptions. A qualitative embedded single-case study was conducted in Raja Ampat Regency, Sorong Regency, Tambrauw Regency, and Sorong City. Data were collected through in-depth interviews with 22 purposively-selected informants, participant observation, and document analysis, analysed thematically through open coding, axial coding, actor network mapping, and cross-category synthesis. The policy network has formed but operates with structural asymmetries. Formal bureaucratic actors occupy central positions (94% forum access; 87% agenda influence) while fisher cooperatives remain peripheral (29% and 12%). Resources are concentrated: planners and technical agencies control 87–94% of administrative and informational resources, while customary institutions control 88% of social-normative legitimacy with limited material access. Six regulatory regimes operate in parallel without synchronisation; perceptions diverge sharply between bureaucratic (policy coherence), indigenous (justice), fisher (livelihood), and business (market certainty) frames. The principal challenge is not the absence of actors, forums, or rules, but the architecture of an asymmetric, fragmented network unable to consolidate collective understanding. Strengthening coastal economies through the blue economy requires restructuring relations, redistributing strategic resources, harmonising plural rules, and transforming divergent perceptions into shared understanding.